Pharmacotherapy for psychologists : prescribing and collaborative roles - McGrath, Robert E., 1956-; Moore, Bret A. (American Psychological Association, 2010)
"This volume provides a snapshot of the professional issues surrounding prescriptive authority, medical collaboration, and practical issues associated with prescribing. It will be useful to those involved in legislative efforts, psychologists who are considering completing the training required to become a medical or prescribing psychologist, and those currently prescribing. It will also be a resource for those who do not decide to pursue prescriptive authority but are interested in becoming better collaborators around medication issues with those who do prescribe. The book comprises four parts. Part I covers the rationale for prescriptive authority (Chapter 1) and key issues in the history of the prescriptive authority movement, including the most recent training guidelines used today (Chapter 2) and the Department of Defense Psychopharmacology Demonstration Project (Chapter 3). More general histories of the prescriptive authority movement are already available elsewhere (see Fox, 2003; McGrath, in press). Part II covers general practice issues, including the challenges of day-to-day pharmacotherapy practice (Chapter 4), ethical considerations of pharmacotherapy (Chapter 5), the integration of psychotherapy and pharmacotherapy (Chapter 6), and the evaluation of drug research (Chapter 7). Part III describes issues related to prescribing in specific settings and with specific populations, including private practice (Chapter 8), primary care clinics (Chapter 9), schools (Chapter 10), and public health agencies (Chapter 11). Finally, Part IV provides ideas for getting prescriptive authority laws passed (Chapter 12) and the future of prescribing psychology (Chapter 13)"--Introduction. (PsycINFO Database Record (c) 2010 APA, all rights reserved).